'Ateliers d'artistes' (1898): an advertorial for the 'lady readers' of the Figaro illustré. Issue 4 (2nd October 2018) - Esner, Rachel
ABSTRACT: This article examines the text and imagery of an article entitled 'Ateliers d'artistes, ' a series of studio visits conducted by the critic François Thiébaut-Sisson in 1898 and published in the Figaro illustré . The series is interesting for a number of reasons, but most importantly because the author makes an explicit appeal to the female readers of the magazine. This appeal is set in the context of the construction of women as consumers (in this case, specifically as consumers of art) and female readership of the illustrated press, and analyzed as an early form of 'advertorial, ' designed to encourage women to purchase the work of the artists visited. At the same time, the series serves to further the commercial interests of the painters discussed, and to consolidate certain stereotypes surrounding the artist's studio.